Efeito da oxigenação hiperbárica e do laser de baixa potência no reparo e biomecânica em osso de ratos com diabetes mellitus tipo I - Limirio, Pedro Henrique Justino Oliveira (2018)
Chronic hyperglycemia due to type 1 diabetes mellitus affects multiple organs interfering in the quality of patients’ life with the disease. In bone, this condition changes bone metabolism, compromising regeneration and bone biomechanical properties. Supporting therapies, such as Low-Level Light (LLLT) and hyperbaric oxygen therapy (HBO) have been proposed to promote bone regeneration or improve tissue conditions. The aim of the present study was to evaluate the effect of LLLT and HBO on microarchitecture and biomechanics bone of rats with type 1 diabetes mellitus (T1DM). Analyzes were performed using computerized micro-tomography (MicroCT), histological and histomorphometric, biomechanical and Fourier transform infrared spectroscopy (FTIR). The results showed that diabetes significantly compromised the bone regeneration, with reduction bone neoformation, trabeculae number and bone volume. T1DM also change the organic and inorganic matrix compounds and mechanical bone properties (maximum strength, energy and stiffness). The therapies used, LLLT and HBO reduced the deleterious effects of diabetes, especially those related to bone neoformation, mechanical properties and ratio between organic and inorganic material. It is concluded that type 1 diabetes mellitus compromises bone regeneration and biomechanical properties; and LLLT and HBO reduce the deleterious effects of T1DM.